Intersectional experiences of discrimination in a low-resource urban community: An exploratory latent class analysis - Earnshaw, Valerie A.; Rosenthal, Lisa; Gilstad-Hayden, Kathryn; Carroll-Scott, Amy; Kershaw, Trace S.; Santilli, Alycia; Ickovics, Jeannette R. (Journal of Community and Applied Social Psychology, 2018)
There have been increasing calls for the application of an intersectionality framework to understand and address discrimination and health inequities among diverse communities. Yet there have been theoretical debates regarding to whom intersectionality applies and how intersectional experiences of discrimination are associated with health outcomes. The current study aimed to contribute to these theoretical debates and inform practical applications to reduce health inequities. Data were drawn from a community health survey in New Haven, CT (N=1,293 adults) and analysed using latent class analysis. Results yielded 4 classes. Members of the 4 classes were similar sociodemographically. Three classes of participants reported experiencing discrimination, and members of these classes had greater stress, higher rates of smoking and sleep disruption, and worse overall health than members of the class reporting no discrimination. Members of 2 classes made multiple, or intersectional, attributions for discrimination, and members of these classes reported the most frequent discrimination. Findings suggest that community members who are sociodemographically similar may have diverse discrimination experiences. Multilevel interventions that address multiple forms of discrimination (e.g., racism and sexism) may hold promise for reducing discrimination and, ultimately, health inequities within low-resource urban community settings.
17 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/032-249-301-742-222 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: adult; article; dept.pch; discrimination; female; health inequities; human; human experiment; intersectionality; latent class analysis; major clinical study; male; peer-reviewed; public health; racism; sexism; sleep; smoking; stress; theoretical study; urban population

Bridging the response to mass shootings and urban violence: exposure to violence in New Haven, Connecticut - Santilli, Alycia; Duffany, Kathleen O'Connor; Carroll-Scott, Amy; Thomas, Jordan; Greene, Ann; Arora, Anita; Agnoli, Alicia; Gan, Geliang; Ickovics, Jeannette (American Journal of Public Health, 2017)
We have described self-reported exposure to gun violence in an urban community of color to inform the movement toward a public health approach to gun violence prevention. The Community Alliance for Research and Engagement at Yale School of Public Health conducted community health needs assessments to document chronic disease prevalence and risk, including exposure to gun violence. We conducted surveys with residents in six low-income neighborhoods in New Haven, Connecticut, using a neighborhood-stratified, population-based sample (n=1189; weighted sample to represent the neighborhoods, n = 29 675). Exposure to violence is pervasive in these neighborhoods: 73% heard gunshots; many had family members or close friends hurt (29%)or killed (18%)by violent acts. Although all respondents live in low-income neighborhoods, exposure to violence differs by race/ ethnicity and social class. Residents of color experienced significantly more violence than did White residents, with a particularly disparate increase among young Black men aged 18 to 34 years. While not ignoring societal costs of horrific mass shootings, we must be clear that a public health approach to gun violence prevention means focusingonthedualepidemicofmass shootings and urban violence.
28 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/022-267-527-707-864 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Adolescent; Adult; African American; African Americans; Aged; Caucasian; Connecticut; European Continental Ancestry Group; Exposure to Violence; Female; Humans; Male; Mass Casualty Incidents; Middle Aged; Poverty Areas; Prevalence; Risk Factors; Self Report; Surveys and Questionnaires; Urban Population; Wounds; Gunshot; adolescent; adult; aged; dept.pch; ethnology; exposure to violence; female; gunshot injury; human; male; mass disaster; middle aged; poverty; prevalence; questionnaire; risk factor; self report; statistics and numerical data; urban population